TINGKAT ADAPTASI MASYARAKAT TERHADAP BENCANA GUNUNG API LOKON DI KOTA TOMOHON - Sanger, Arwinsky S; Waani, Judy O.; Franklin, Papia J. C. (MEDIA MATRASAIN, 2021)
Facts prove that the magnitude of the potential for volcanic vulnerability in Indonesia can be identified from the location of the area and geographical position, where its existence is in the path of the meeting of tectonic plates with active volcanic lines or known as the ring of fire. North Sulawesi itself has Â± 7 active volcanoes, one of them is Mount Lokon in Tomohon City. One of the most devastating eruptions that brought huge losses due to the eruption of Mount Lokon occurred decades ago, precisely in 1991, Mount Lokon erupted on a large scale. Therefore, this research is needed to determine the adaptation capacity and level of adaptation of the community to face the threat of danger from the Lokon volcano. The purpose of this study was to identify existing conditions, analyze the adaptation capacities, and analyze the level of adaptation of the community in North Tomohon District. This research uses descriptive quantitative research methods with Geographic Information Systems (GIS) analysis methods and uses the scoring method. The results showed that the adaptation capacity for physical, social, and economic aspects got a high score, this indicated that the community was able to adapt, while for the adaptation level, based on the classification score the score was 2 in the adaptation level theory, which showed that the intermediate level of excitability was the right level that could maximized behavior.